Legal studiesWomen's political representation in the regional people's representative council based on law number 7 of 2017 concerning elections in Indonesia - Komalasari, Dewi; Jiwantara, Firzhal Arzhi; Hasanah, Siti (Journal of Law Science, 2025)
Women and men have the same position in politics, Women's involvement has the significance of participating in parliament in the process of policy-making and development participation as well as to enrich the perspectives and experiences that shape public policy. The purpose of this study is to find out how women are represented in political affairs in legislative elections in Indonesia. The method used in this study is a normative research method with a statute approach and a conceptual approach in a qualitative descriptive analysis, the data used in this study is sourced from primary legal materials, secondary legal materials and library research results from various references. The results of the study show that women's representation is increasing, in line with expectations for existing policies on women's representation because there are many issues related to women that require women's representation in legislative institutions. Law Number 7 of 2017 concerning General Elections has expressly stipulated that every political party is obliged to nominate at least 30% of women.